The Influence of Supervision, Competence, Leadership, and Motivation on Mathematics Teachers Productivity in Bengkulu - Zulkarnain, Zulkarnain; Warlizasusi, Jumira; Harmi, Hendra (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the impact of academic supervision, professional competence, instructional leadership, and work motivation on work productivity within the framework of the Integrative Model of Organizational Behavior. A quantitative approach, utilizing a survey method, was employed with 60 mathematics teachers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that professional competence (β = 0.337, p = 0.007), instructional leadership (β = 0.262, p = 0.018), and work motivation (β = 0.363, p = 0.001) have a positive and significant effect on teacher productivity. In contrast, supervision has no direct effect on productivity (β = 0.104, p = 0.138), but it does significantly influence motivation (β = 0.218, p = 0.037). Motivation significantly mediated the relationship between competence and productivity (β = 0.081, p = 0.043), but did not mediate the relationship between supervision or leadership and productivity. This finding underscores the importance of enhancing teacher competence and motivation to enhance productivity. The implications of this study suggest that developing professional competence, instructional leadership, and work motivation should be a primary focus for improving teacher productivity.